PERSONALIA : On the Seventy-Fifth Birthday of Sergei Nikolaevich Bagayev. (1st November 2016) - Alferov, Zh I; Andreev, A F; Aseev, A L; Vinogradov, E A; Dianov, E M; Krokhin, O N; Laverov, N P; Litvak, A G; Panchenko, V Ya; Sergeev, A M; Skrinsky, A N; Shcherbakov, I A
Abstract: Academician Sergei Nikolaevich Bagayev, an eminent physicist and science manager, director of sciences at the Institute of Laser Physics (ILP), Siberian Branch (SB), Russian Academy of Sciences (RAS), was born on 9 September 1941 in Novosibirsk.